A master in disguise? The rediscovery of Misumena bicolor Simon, 1875 (Araneae: Thomisidae) - Bach, Alexander; Lauterbach, Stephan; Astrin, Jonas J.; Thorns, Hans-Jürgen; Bauer, Tobias (Zootaxa, 2024)
Misumena bicolor Simon, 1875, an enigmatic species known only from the male holotype collected on Corsica (France), has remained elusive since its initial description. In this study, we report new occurrences of M. bicolor from Sardinia (Italy) and Bavaria (Germany) based on male material, considerably expanding its known distribution. Employing an integrative taxonomic approach encompassing both morphological and COI (barcode) analyses, we confirm M. bicolor as a valid species. As the male of M. bicolor apparently has a distinct coloration, we complement the known distributional data with possible sightings of photographic observations from various naturalist portals and hereby provide additional evidence for the establishment of the species on the French mainland and in Germany.